Respuesta :
Answer:
Step-by-step explanation:
2(9a - 6) = 2*9a - 2*6 = 18a - 12
Yes, it is equivalent.
6*(3a-2) = 6*3a - 6*2 = 18a - 12
Yes, it is equivalent.
-3(6a+4)= -3*6a + 4*(-3) = -18a - 12
No, not equivalent
3(6a+4) = 3*6a + 3*4 = 18a + 12
No, not equivalent
-3(4-6a) = -3*4 - 6a*(-3 ) = -12 + 18a = 18a - 12
Yes, it is equivalent.
Answer:
2(9a - 6), 6(3a – 2) and -3(4 – 6а)
Step-by-step explanation:
2(9a - 6) = 2 × 9a + 2 × (-6)
= 18a - 12
6(3a - 2) = 6 × 3a + 6 × (-2)
= 18a - 12
- 3( 4 - 6a ) = - 3 × 4 + (-3) × (- 6a)
= - 12 + 18a = 18a - 12